Production of biodiesel from mixed waste vegetable oils using Ferric hydrogen sulphate as an effective reusable heterogeneous solid acid catalyst - Alhassan, Fatah H.; Yunus, Robiah; Rashid, Umer; Sirat, Kamaliah; Islam, Md Aminul; Lee, Hwei Voon; Yap, Taufiq Yun Hin (Elsevier, 2013)
Biodiesel production by simultaneous esterification and transesterification of waste oil with methanol has been studied in a heterogeneous system using solid ferric hydrogen sulphate [Fe (HSO4)3] acid catalyst. The catalyst was prepared by displacement reaction followed by calcination at 400 °C for 3 h. The prepared catalyst was characterized using X-ray diffraction (XRD), Fourier transform infrared spectrometer (FT-IR), Brunner-Emmett-Teller surface area measurement (BET), thermal gravimetric analyzer (TGA) and temperature-programmed desorption of NH3 (TPD - NH3). Furthermore, the dependence of the conversion of mixed waste oil on the reactions variables such as the molar ratio of methanol/oil, the amount of catalysts used, reaction temperatures, reusability were also investigated. The catalyst was reused many times with slight loss in activity and the maximum yield of 94.5% was achieved at the optimized conditions of reaction temperature of 205 °C; stirring speed of 350 rpm, 1:15 molar ratio of oil to alcohol and 1% w/w catalyst loading.